An Analysis of Student’s Needs for Media For Learning Vocabulary - -, Mursyidah; Melinda Septadella; Wulandari, Fitri; Pratiwi, Neli (English Education Program, Education Faculty, Universitas Nurul Huda, 2023)
Learning English vocabulary is very important in the development of students at school. By mastering English vocabulary, students can pronounce and intonation properly and correctly. This research is a qualitative type of research wit h descriptive qualitative methods and was carried out at MI Mathla’ul Anwar Sinarbetung. Data collection techniques used are observation and interviews. Data were analyzed through data reduction, data presentation and drawing conclusion. The objective of this article was to describe student’s difficulties in remembering and increasing vocabulary at fourth grade students of MI Mathla’ul Anwar Sinarbetung. The population was the fourth grade students of MI Mathla’ul Anwar Sinarbetung, with the total number of the students are 22 students. The sample was 17 students taken through convenience sampling technique. The result of research showed that the students need learning media to facilitate vocabulary learning with media criteria that are uniquely designed, pictorial, fun and easy to understand.